Evaluation of organizational culture in companies for fostering a digital innovation using q-rung picture fuzzy based decision-making model - Abdullah Hussein Abdullah Al-Amoodi (Tanjung Malim, 2023)
Evaluation of organizational culture in companies for fostering a digital innovation using q-rung picture fuzzy based decision-making model by Abdullah Hussein Abdullah Al-Amoodi